2022
DOI: 10.3389/fcvm.2022.850447
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Injury Predicts Risk of Short-Term All-Cause Mortality in Patients With COVID-19: A Dose–Response Meta-Analysis

Abstract: ObjectivePredictive value of myocardial injury as defined by elevated cardiac tropnins (cTns) in patients with COVID-19 has not been fully investigated. We performed a meta-analysis to evaluate the dose–response relationship between myocardial injury and short-term all-cause mortality.MethodsPubmed, Embase, and the Cochrane Library database were searched for all the studies which evaluated the relationship between cTns and the risk of short-term all-cause mortality in patients with COVID-19.ResultsCompared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
2
6
0
1
Order By: Relevance
“…During the early stages of the pandemic, an alarming incidence of myocardial injury was detected among critically ill COVID-19 patients [2][3][4][5][6], leading to the elaboration of hypotheses to explain this incidence. Among them, it was proposed that pulmonary and cardiovascular damage could be mediated by a functional cell entry receptor of SARS-CoV-2, a type 2 Angiotensin Converting Enzyme receptor (ACE2), which is abundantly expressed on the surface of cells in the lungs and cardiovascular system [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the early stages of the pandemic, an alarming incidence of myocardial injury was detected among critically ill COVID-19 patients [2][3][4][5][6], leading to the elaboration of hypotheses to explain this incidence. Among them, it was proposed that pulmonary and cardiovascular damage could be mediated by a functional cell entry receptor of SARS-CoV-2, a type 2 Angiotensin Converting Enzyme receptor (ACE2), which is abundantly expressed on the surface of cells in the lungs and cardiovascular system [19].…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial injury, defined as an elevated serum troponin level higher than the 99th percentile of a reference population, is a common finding in hospitalized COVID-19 patients [1]. Previous studies have reported the frequency of myocardial injury in COVID-19 patients ranges from 9.2 to 63.5% [2][3][4][5][6], with a well-established association with worse outcomes and increased mortality [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an increasing amount of data suggests that during COVID-19, not only is the respiratory system involved but data also demonstrate that the cardiovascular system may be affected which can lead to myocardial injury. These patients tend to have a significantly worse prognosis than those without the myocardial injury ( 6 8 ). So far, it has been proven that the inflammatory and immune response due to viral infection has also had a role in the pathogenesis of an acute MI ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, we do know that the short-term cardiovascular effects on the long-term consequences in COVID-19 patients are related to myocardial injuries detected in the acute phase [ 12 , 13 ]. It is essential to recognise that, in some cases, a myocardial injury will persist once the acute phase of the infection has passed [ 14 ].…”
mentioning
confidence: 99%